China’s belt and road initiative: A soft power influence in Africa - Esther Victoria Ekoko; E. A. Orhero; A. F. Ikenga (Department of Accounting Universitas PGRI Yogyakarta, 2025)
China’s Belt and Road Initiative (BRI) has emerged as a strategic tool of soft power, shaping diplomatic, economic, and cultural relations between China and Africa. This paper examines how the BRI enhances China’s influence on the continent through infrastructure investments, trade partnerships, and governance cooperation. It explores the economic benefits of the initiative, including job creation, enhanced connectivity, and industrial development, while also addressing concerns regarding debt sustainability, environmental impact, and political dependence. Furthermore, the research assesses African perceptions of the BRI, analyzing both its long-term benefits and potential risks. Additionally, it highlights the role of cultural and educational exchanges in strengthening China’s soft power presence in Africa. The findings reveal that while the BRI significantly contributes to Africa’s development, it also raises challenges related to governance, economic dependence, and transparency. The study concludes that for the BRI to be mutually beneficial, both China and African nations must adopt sustainable financing mechanisms, prioritize local economic participation, and foster deeper cultural engagements. These measures will ensure that the initiative supports Africa’s long-term growth while advancing China’s soft power objectives.